Comparison of Family Awareness, Emotional Climate, and Emotional Divorce among Married Men and Women in Yazd - Atefeh Ahmadi Sanori; Mohammad Hossein Sorbi; Sima Abdi Kazaj; Nahid Ardian (Journal of Social Behavior and Community Health, 2023)
Background: This research was conducted with the aim of comparing family awareness, emotional climate, and emotional divorce among married men and women in Yazd. Methods: The study was of an analytical type and was conducted cross-sectional, with the participation of 250 married men and women who had sought counseling services in Yazd due to family problems. The sampling method in this research was purposive. Data were collected using a demographic form, the Family Awareness Scale (FAS), the Emotional Climate Scale for Couples (ECSC), and the Emotional Divorce Scale (EDS). The data were analyzed using SPSS-21 software. Results: Pearson correlation coefficients showed a significant negative relationship between family awareness and emotional climate (r = -0.71) and emotional divorce (r = -0.70), and a significant positive relationship between emotional climate and emotional divorce (r = 0.86, p < 0.01). Independent t-test showed that women had lower family awareness than men. Furthermore, women scored higher on emotional climate and emotional divorce compared to men, and these results were statistically significant (p < 0.01). Conclusion: The results indicate that women have lower family awareness than men, which, in addition to creating a tension-inducing emotional climate, increases the likelihood of emotional divorce. Therefore, it is recommended for couple’s therapists to develop practical programs to enhance family awareness skills as an effective step in reducing emotional divorce and increasing emotional climate between spouses.